2015
DOI: 10.1103/physrevb.92.134109
|View full text |Cite
|
Sign up to set email alerts
|

Directin situmeasurement of coupled magnetostructural evolution in a ferromagnetic shape memory alloy and its theoretical modeling

Abstract: Ferromagnetic shape memory alloys (FSMA) have shown great potential as active components in next generation smart devices due to their exceptionally large magnetic-fieldinduced strains and fast response times. During application of magnetic fields in FSMAs, as is common in several magnetoelastic smart materials, there occurs simultaneous rotation of magnetic moments and reorientation of twin variants, resolving which although critical for design of new materials and devices, has been difficult to achieve quant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 79 publications
0
2
0
Order By: Relevance
“…They concluded that the magnetization becomes weaker as the temperature increases due to the decreasing magnetic ordering, and that there is no intermartensitic transformation in the investigated alloy. Pramanick et al [69] employed polarized neutron diffraction to establish a correlation between the rotation of magnetic moments and the twin-reorientation phenomena in a Ni 2 Mn 1.14 Ga 0.86 single crystal. Lázpita et al [70] performed polarized neutron diffraction measurements to determine the influence of the atomic positions within the crystal unit cell on the magnetic coupling between atoms in the austenitic phase of Ni 51.9 Mn 26.2 Ga 21.9 , and in the martensitic phase of Ni 52.6 Mn 26.9 Ga 20.5 , the latter presenting a non-modulated tetragonal phase.…”
Section: Polarized Neutron Diffractionmentioning
confidence: 99%
“…They concluded that the magnetization becomes weaker as the temperature increases due to the decreasing magnetic ordering, and that there is no intermartensitic transformation in the investigated alloy. Pramanick et al [69] employed polarized neutron diffraction to establish a correlation between the rotation of magnetic moments and the twin-reorientation phenomena in a Ni 2 Mn 1.14 Ga 0.86 single crystal. Lázpita et al [70] performed polarized neutron diffraction measurements to determine the influence of the atomic positions within the crystal unit cell on the magnetic coupling between atoms in the austenitic phase of Ni 51.9 Mn 26.2 Ga 21.9 , and in the martensitic phase of Ni 52.6 Mn 26.9 Ga 20.5 , the latter presenting a non-modulated tetragonal phase.…”
Section: Polarized Neutron Diffractionmentioning
confidence: 99%
“…Although the magnetic and mechanical properties of FSMA have been widely investigated in the past decades, the correlation between the macro-response and the micromagnetic domain evolution is still vague due to the limitation of experimental characterizations. For example, neutron scattering experiment has shown its great power in the study of FSMAs during the last decades [33][34][35][36], however, the experimental results are usually from statistical averages. Thereby, detailed microstructures in the associated experiments are not clear.…”
Section: Introductionmentioning
confidence: 99%